Vitamin C supplementation in aquaculture activities - de Lima Costa Gomes, Jeane; Blank do Amaral, Aline Monique; Teixeira Marins, Aline; Menezes, Charlene; Rosso Storck, Tamiris; Martinelli, Suziane; Picolli da Silva, Leila; Loro, Vania Lucia; Clasen, Bárbara (Cadernos de Ciência & Tecnologia, 2020)
This study investigated the effects of different levels of vitamin C in diet of fish with oxidative stress biomarkers and hematological parameters of silver catfish. Juvenile fish were divided into three groups, and fed with different amounts of vitamin C: 1) 0, 2) 500, and 3) 1,000 mg kg-1. Ten fish per group were collected at 0, 14, and 28 days after the beginning of the experiment. Liver catalase activity increased in group 1 after 28 days. The GPx activity in gills decreased in all groups, and the hepatic GPx activity increased in groups fed with vitamin C. SOD hepatic activity and NPSH levels in gills and liver were not affected. In all groups, the GST activity in gills decreased, and the GST activity in liver increased. The levels of lipid peroxidation decreased in liver and gills for groups 2 and 3. This study’s results indicate that both diets with 500 or 1,000 mg/kg of vitamin C contributed to the decrease in the oxidative damage of Rhamdia quelen, suggesting that vitamin C supplementation in the present experimental model could be useful in aquaculture to overcome possible oxidative changes induced by adverse environmental conditions.